STAMP: statistical analysis of taxonomic and functional profiles - Parks, Donovan H.; Tyson, Gene W.; Hugenholtz, Philip; Beiko, Robert G. (Bioinformatics (Oxford, England), 2014)
STAMP is a graphical software package that provides statistical hypothesis tests and exploratory plots for analysing taxonomic and functional profiles. It supports tests for comparing pairs of samples or samples organized into two or more treatment groups. Effect sizes and confidence intervals are provided to allow critical assessment of the biological relevancy of test results. A user-friendly graphical interface permits easy exploration of statistical results and generation of publication-quality plots. Availability and implementation: STAMP is licensed under the GNU GPL. Python source code and binaries are available from our website at: http://kiwi.cs.dal.ca/Software/STAMP Contact:  donovan.parks@gmail.com Supplementary information:  Supplementary data are available at Bioinformatics online.